Youth involvement in alcohol and drug prevention: A systematic review - Aresi, G.; Ferrari, V.; Marta, E.; Simões, F. (Journal of Community and Applied Social Psychology, 2023)
To review and analyse how youth involvement was conceptualised and applied in published alcohol and drug preventive interventions. A systematic review of the scientific literature on alcohol and drug prevention where young people (18–29 years old) participated at any stage of the intervention was conducted. We searched relevant bibliographic databases and online repositories for peer-reviewed studies published between 2001 and 2021. Twenty-seven articles reporting on studies in different countries and settings and using various intervention strategies were eligible for inclusion. The analysis of the stages of youth involvement and the dimension of power sharing in decision-making showed that only a minority of studies could be considered genuinely youth-led whereas many involved young people merely as implementers of highly controlled research-led interventions. However, the few studies that promoted sustained youth involvement struggled with translating results into rigorously evaluated interventions, thus demonstrating a tension between adoption of effective interventions and support to genuinely participatory processes. Knowledge gaps and implications for practice and research are discussed from a participatory research perspective.